DEMOGRAPHIC CHARACTERISTICS AND BODY MASS INDEX IN OBESE ADOLESCENTS - Nur Aisyah Widjaja; Rendi Aji Prihaningtyas; Meta Herdiana Hanindita; Roedi Irawan (Universitas Airlangga, 2019)
Background: The prevalence of adolescent obesity is increasing in Indonesia. Obesity can reduce the quality of life, especially as most obese adolescents remain obese after they become adult. In obese adolescents, the higher their IMT (intima-media thickness), the higher the risk of cardiovascular disease in adulthood. Purpose: The aim of this study is to analyse the correlation of demographic characteristics with BMI (body mass index) in adolescents with obesity. Methods: This study is a cross-sectional study on adolescents with obesity conducted in the Paediatric Nutrition and Metabolic Disease Clinic of Dr Soetomo General Hospital, Surabaya. The data on demographic characteristics, such as gender, number of siblings, paternal education, maternal education, and maternal occupation, were collected using the interview method. Data on anthropometry were collected to calculate BMI. Obesity is established if it is higher than the 95th percentile, based on CDC percentile of BMI, according to age and sex. Data were analysed using multiple regression. Results: A total of 59 obese adolescents, between 13 and 16 years old, were involved. As many as 49.20% of respondents had one sibling. As many as 52.50% of respondents had a father with a high school education and 44.10% of respondents had mothers with a high school education; 61% of respondents had working mothers. There was no correlation between BMI and demographic characteristics (p> 0.05), except for number of siblings (p = 0.02). Conclusion: In this study, the number of siblings was correlated with BMI. A study with a greater number of obese adolescents and with adolescents who have normal nutritional status is needed to fully assess the influence of demographic characteristics on BMI in obese adolescents.